Experimental Output Regulation of Linear Motor Driven Inverted Pendulum With Friction Compensation - Ping, Zhaowu; Liu, Chenxi; Huang, Yunzhi; Yu, Ming; Lu, Jun-Guo (IEEE transactions on systems, man, and cybernetics. Systems, 2021)
Over the past few decades, the nonlinear output regulation (NOR) theory has attracted extensive attentions in control society. However, few experimental results have been reported about the NOR theory. This article first presents experimental results on discrete-time NOR problem for a linear motor driven inverted pendulum (LMDIP) system. To solve this problem, it is essential to find the solution of the complicated discrete regulator equations (DREs). Moreover, the friction force commonly exists in mechanical systems and cannot be neglected for control systems requiring high precision tracking performance. We present a novel discrete-time controller by combining neural network (NN) approach and friction-feedforward compensation mechanism. Finally, we verify the proposed control algorithm by experiment and make some comparisons with the linear controller.